TEACHER'S ACTIVITY AND STUDENT'S ACTIVITY IN THE TEACHING PROCESS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
The formation of relationships is closely related to the communication of the teacher and educator with an individual child, a team of children and teachers. Relationships and communication skills underlie the adaptation of a novice teacher and educator to teaching. They are also, along with knowledge, professional skills and the general culture of the teacher, the main condition for acquiring pedagogical skills.